THE PROCESS OF UZBEKIZATION IN THE ADMINISTRATIVE SYSTEM OF DISTRICTS IN UZBEKISTAN (20S OF THE 20TH CENTURY) - Shaira Davlatova (Scholar Express Journal, 2023)
This article discusses the localization, Uzbekization policy and its results carried out by the Soviet authorities in the districts of Uzbekistan in the 20th years of the 20th century.
Keywords: Districts; zoning; Uzbekization policy; state apparatus and industry localization policy